Analytical Aspects for Evaluation of Pharmaceutical Products: A Mini- Review - Lustosa, Isadora A.; de Souza Gil, Eric; Kogawa, Ana Carolina (Current Pharmaceutical Analysis, 2022)
Background: The pharmaceutical industry is in constant development, aiming to increase its portfolio, optimizing time, product quality and efficacy along with patient safety. The main goal of developing and validating an analytical method is to achieve a balance between costs and risks within the wide array of technical possibilities in order to assure that the method is capable of meeting its expectations, ensuring effective quality control. Objective: The objective of this mini-review is to discuss the analytical aspects of development and validation for analysis of pharmaceutical products, focusing on the complete evaluation package in a systematic way to demonstrate the optimal performance of the method. Methods and Results: Validation results are obtained following strict protocols, typically starting with the assessment of selectivity/specificity parameters, followed by parameters such as linearity and precision. Moreover, accuracy, detection limit, quantification limit and method robustness are also evaluated. Conclusion: This paper may serve as a guide for the pharmaceutical-chemical laboratory, conceptualizing quality and current analytical needs, according to Green Analytical Chemistry, for the development and validation of reliable methods, ensuring clarity to the analyst and assisting in decision making.
Keywords: pharmaceutical product